2019
DOI: 10.21475/ajcs.19.13.02.p1594
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diversity and population structure of mango (Mangifera indica L.) germplasm based on microsatellite (SSR) markers

Abstract: The assessment of genetic diversity is essential for the conservation and breeding purposes. This study aimed to assess and evaluate the genetic diversity of 116 accessions of mango (Mangifera indica) germplasm using microsatellite markers. The DNA was extracted from young fresh leaf before genotyping using microsatellites to determine the allele size. The analysis of 20 polymorphic microsatellite markers revealed a total of 122 alleles ranging from two (MiIIHR10, MiIIHR21, and MiIIHR25) to 11 alleles per locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(39 reference statements)
1
6
1
Order By: Relevance
“…The PIC value also indicates the level of allele variation (Surapaneni et al 2013). The value is higher than the previous studies conducted by Razak et al (2019), Begum et al (2014), andAzam et al (2019), but lower than the value obtained by Ravishankar et al (2011). The difference in PIC values can be associated with differences in microsatellite allele profiles, the number of accessions studied, varieties, and locations (Surapaneni et al 2013).…”
Section: Microsatellite Analysiscontrasting
confidence: 57%
“…The PIC value also indicates the level of allele variation (Surapaneni et al 2013). The value is higher than the previous studies conducted by Razak et al (2019), Begum et al (2014), andAzam et al (2019), but lower than the value obtained by Ravishankar et al (2011). The difference in PIC values can be associated with differences in microsatellite allele profiles, the number of accessions studied, varieties, and locations (Surapaneni et al 2013).…”
Section: Microsatellite Analysiscontrasting
confidence: 57%
“…While the lowest (one) numbers of amplified bands was recorded in MillHR20a and AJ635178 (Table 2). The results are in agreement with previous reports based on SSR markers developed for Mangifera indica to evaluate mango varieties in India [18,32,33], China [14,34], Indonesia [35], Pakistan [3,36], Maxico [37] and Japan [13].…”
Section: Discussionsupporting
confidence: 93%
“…studies have been reported on the application of different molecular markers with different mango genotypes for genetic diversity analyses such as RAPD (Schnell et al 1995;López-Valenzuela et al 1997;Kumar et al 2001;Karihaloo et al 2003;Rahman et al 2007;Mansour et al 2008;Díaz-Matallana et al 2009;Mansour et al 2014;Ahmedand, Mohamed 2015;Rashed, Maklad 2016;Galal et al 2017;El-Sayed et al 2018;He et al 2021), AFLP (Kashkush et al 2001;Yamanaka et al 2006;Zhang et al 2014;Wang et al 2015;Dang, Chen 2017) and SSR (Duval et al 2005;Honsho et al 2005;Singh et al 2012;Tsai et al 2013;Azmat et al 2016;Lal et al 2017;Ajayi et al 2019;Razak et al 2019;Yamanaka et al 2019). The start codon targeted (SCoT) polymorphism is a simple and effective gene targeted marker technique based on the conserved region surrounding the translation codon ATG (Collard, Mackill 2009).…”
Section: Methodsmentioning
confidence: 99%